Amikacin induces rapid dose‐dependent apoptotic cell death in equine chondrocytes and synovial cells in vitro. (21st February 2020) - Pezzanite, Lynn; Chow, Lyndah; Soontararak, Sirikul; Phillips, Jennifer; Goodrich, Laurie; Dow, Steven
Abstract: Background: Equine veterinarians frequently inject aminoglycoside antibiotics intra‐articularly, either to treat septic arthritis or for prophylaxis with other medications when injecting joints for osteoarthritis. Although aminoglycosides have been demonstrated to be toxic to equine mesenchymal stem cells (MSC), their effects on resident joint cells have not been previously investigated. Moreover, safe and effective intra‐articular doses have not been defined. Objectives: To determine effects of concentration, duration of exposure, pH and the presence of synovial fluid on the cytotoxic effects of amikacin on equine chondrocytes, synoviocytes and bone marrow– and adipose‐derived MSC. Study design: In vitro experimental study. Methods: Four cell types were harvested from three donor horses and plated in triplicate wells for 48 hours prior to the addition of amikacin. The effects of amikacin on cell viability were assessed for different exposure times, concentrations and with pH buffered or unbuffered in media, as well as in the presence of synovial fluid. Cell metabolism/viability was assessed by colorimetric MTT assay. Cell proliferation was assessed by live cell imaging. Cell viability was assessed using trypan blue and dimeric cyanine nucleic acid stain (yoyo‐1). To determine the mechanism of cell death, apoptosis was evaluated using Annexin V and 7AAD staining with flow cytometric quantification. Induction of apoptotic cell death pathways was assessed using caspase‐3 expression. Results: Amikacin is cytotoxic to equine joint cells and MSC in a rapid, dose‐dependent, pH‐independent manner, which occurs primarily by apoptosis. Amikacin cytotoxicity was not mitigated by the addition of synovial fluid in vitro. Main limitations: Further studies are necessary to determine whether these in vitro results predict joint injury in live animal models. Conclusions: Amikacin at clinically applied doses induces rapid, pronounced cell death of equine joint cells. These findings suggest that amikacin doses currently used intra‐articularly should be reconsidered pending in vivo joint titration studies.